Designing a Web-Based Raw Material Purchase Accounting Information System - Yola Septiani; Nurhaliza Sukma Fadila; Sayyidah Nabila Azahra (International Journal of Research and Applied Technology (INJURATECH), 2023)
Kerupuk Pangsit Adem Ayem is one of the manufacturing companies engaged in snacks. To meet the inventory, the company must make purchases of raw materials. Purchasing is a continuous activity for the company and is the main proposal in production. The design of an accounting information system for purchasing raw materials on Kerupuk Pangsit Adem Ayem can facilitate the process of purchasing raw materials via the web and can produce financial report information easily and quickly. The system design method used in this study used survey methods and descriptive methods. The data collected in conducting this study is in the form of qualitative data. The raw material purchase accounting information system can be used as a means of facilitating the determination of raw material purchases for production and financial reporting in the form of reports on cost of goods produced, so that the information produced is more precise and accurate.